2014
DOI: 10.1371/journal.pone.0101996
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Genome Sequences from Plant Pathogenic Rhodococcus Reveals Genetic Novelties in Virulence Loci

Abstract: Members of Gram-positive Actinobacteria cause economically important diseases to plants. Within the Rhodococcus genus, some members can cause growth deformities and persist as pathogens on a wide range of host plants. The current model predicts that phytopathogenic isolates require a cluster of three loci present on a linear plasmid, with the fas operon central to virulence. The Fas proteins synthesize, modify, and activate a mixture of growth regulating cytokinins, which cause a hormonal imbalance in plants, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
85
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(87 citation statements)
references
References 91 publications
(127 reference statements)
1
85
0
Order By: Relevance
“…Determination of the fresh weight of the plants revealed that D188 decreased the biomass of the plants to 10% of that of the non-infected controls, whereas plants infected with either PBTS1 or PBTS2 reached a fresh weight that was approximately 20% of that of the uninfected controls (Figure 2E). In line with these findings, when seedlings of N. benthamiana, which has also been used as a host for leafy gall inducers (Creason et al, 2014), were planted in substrate co-inoculated with PBTS1 and PBTS2, their growth was severely stunted, flowering was delayed, and the number of flowers was reduced (Figure 2F).…”
Section: The Pathogenicity Of Pbts1 and Pbts2 Is Linked With The Pressupporting
confidence: 69%
See 3 more Smart Citations
“…Determination of the fresh weight of the plants revealed that D188 decreased the biomass of the plants to 10% of that of the non-infected controls, whereas plants infected with either PBTS1 or PBTS2 reached a fresh weight that was approximately 20% of that of the uninfected controls (Figure 2E). In line with these findings, when seedlings of N. benthamiana, which has also been used as a host for leafy gall inducers (Creason et al, 2014), were planted in substrate co-inoculated with PBTS1 and PBTS2, their growth was severely stunted, flowering was delayed, and the number of flowers was reduced (Figure 2F).…”
Section: The Pathogenicity Of Pbts1 and Pbts2 Is Linked With The Pressupporting
confidence: 69%
“…The host range of these bacteria encompasses a broad spectrum of mostly herbaceous dicotyledonous plants, although some woody plants and few monocotyledons are sensitive as well (Putnam and Miller, 2007;Depuydt et al, 2008b). Key to symptom development is the bacterial production of an array of cytokinins via gene products of the fasciation (fas) operon encoded on a linear virulence plasmid in most pathogenic isolates (Crespi et al, 1992;Pertry et al, 2009Pertry et al, , 2010Francis et al, 2012;Creason et al, 2014;Radhika et al, 2015;Jameson et al, 2019) and the concomitant modification of the hormone landscape of the infected plant (Depuydt et al, 2008a(Depuydt et al, , 2009aStes et al, 2011aStes et al, , 2012Stes et al, , 2015Jameson et al, 2019). Additionally, the pathogenic model strain D188 possesses a chromosomal locus vic (virulence in chromosome) implicated in symptom persistence that encodes a malate synthase believed to be involved in the catabolism of leafy gall-specific nutrients (Vereecke et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequent investigations will focus on expression of RfMT1 and RfMT2 and levels of methylated cytokinins [newly identified from Rhodococcus-infected plant tissues by Radhika et al (2015)], as well as the methylthio-and cis-forms of the cytokinins. We will then be able to compare, in pea, the impact of the methylated cytokinins (Radhika et al, 2015), with the 'trickwith-the-mix' hypothesis developed based on experiments with R. fascians and arabidopsis (Pertry et al, 2009(Pertry et al, , 2010, with the suggestion by Creason et al (2014) that only one cytokinin type (the iP-type) is necessary for disease symptoms to be manifested.…”
Section: Discussionmentioning
confidence: 99%